Alat Gerak hewan dan Manusia Dikemas dalam Media Pop-Up Book - Rahayu, Ni Nyoman Diana; Margunayasa, I Gede; Fakhriyah, Fina (International Journal of Elementary Education, 2020)
This research is based because the book used by teachers and students in the learning process is still limited, especially in the science material and the display of the book is also less attractive, making it difficult for teachers to explain the material and students become less understanding about the material described, causing student understanding to decrease, in addition, the lack of media use and development also underlies this research. This research aims to develop pop-up book media on the topic of animal and human motion equipment. This research is a development research that uses ADDIE development model which consists of stages (1) analysis, (2) design, (3) Development, (4) implementation, and (5) evaluation. However, this research is only limited to the development stage., the stages of implementation and evaluation were not carried out due to time, resources and financial limitations. The subject in this research is the pop-up book media on the topic of animal and human motion equipment, while the object of this study is the validity of the pop-up book media on the topic of animal and human motion equipment. The method used in the assessment of pop-up book media is a questionnaire method by providing an assessment sheet to two teachers and two lecturers who are experts in their fields. In the validity test activities of the pop-up book media produces data in the form of numbers which are calculated on average scores then converted into a five-scale guideline table. The average value of the validity of the pop-up book media obtained was 4.87 with very good qualifications. Based on this analysis it can be concluded that the development of the pop-up book media on the topic of animal and human motion equipment declared valid.